Penerapan Media Pop Up Book Pada Pembelajaran IPAS Materi Ayo Berkenalan Dengan Bumi Kita Pada Siswa Kelas 5 SD Negeri 2 Kalirejo - Unialicha Syarifah Kamila; Sukartono (Jurnal Elementaria Edukasia, 2023)
Low student interest in learning is a cause that comes from teachers paying less attention to learning facilities for students at school, often we find that the learning that teachers provide to students is still very simple, this can affect student interest in carrying out learning. The purpose of this study is to describe the planning, implementation, supporting factors and inhibiting factors of the application of pop up book media in learning IPAS material Let's Get Acquainted with Our Earth in grade V students of SDN 2 Kalirejo.  The type of research used is qualitative with a descriptive approach design. Data collection techniques through observation, interviews, and documentation. The research place was conducted at SD Negeri 2 Kalirejo. The research time started from August 2023 to November 2023. Data validity uses triangulation of sources and techniques. Data analysis techniques use data analysis steps according to Miles and Huberman which consist of data collection, data reduction, data presentation, conclusions. The results of this study indicate that by using Pop Up Book learning media on the learning IPAS, students look enthusiastic in participating in learning, students are more focused and active to answer the material presented, students feel happy with learning using pop up book media, the application of pop up book media has succeeded in motivating students, the material conveyed is easily understood by students.